How Is Existential Threat Related to Intergroup Conflict? Introducing the Multidimensional Existential Threat (MET) Model - Hirschberger, Gilad; Ein-Dor, Tsachi; Leidner, Bernhard; Saguy, Tamar (Frontiers in Psychology, 2016)
Existential threat lies at the heart of intergroup conflict, but the literature on existential concerns lacks clear conceptualization and integration. To address this problem, we offer a new conceptualization and measurement of existential threat. We establish the reliability and validity of our measure, and to illustrate its utility, we examine whether different existential threats underlie the association between political ideology and support for specific political policies. Study 1 (N = 798) established the construct validity of the scale, and revealed four distinct existential threats: personal death, physical collective annihilation, symbolic collective annihilation, and past victimization. Study 2 (N = 424) confirmed the 4-factor structure, and the convergent and discriminant validity of the scale. Study 3 (N = 170) revealed that the association between a hawkish political ideology and support for hardline policies was mediated by past victimization, whereas the association between a dovish political ideology and conciliatory policies was mediated by concerns over collective symbolic annihilation. Study 4 (N = 503) conceptually replicated the pattern of findings found in Study 3, and showed that at times of conflict, physical collective annihilation concerns also mediate the relationship between hawkish ideologies and support for hardline policies. In both Studies 3 and 4, when controlling for other threats, personal death did not play a significant role. These results underscore the need to consider the multidimensional nature of existential threat, especially in the context of political conflict.